Naakpi Kuunwena - Koyukuo village (Lawra District), Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Naakpi Kuunwena is a farmer from the village Koyukuo in Ghana, who talks in the video about the changes in the climate. He is especially concerned about the changed rainfall pattern and the lack of water and irrigation infrastructure such as a dam. An irrigation system is needed to deal with the changed rainfall patterns. Even though an NGO has drilled a borehole in his fields, it dries up after five buckets. He uses the water from the nearby river, but it is also drying up during the dry months, making it an unreliable water source.